Impact of AJCC 8th edition staging system and definitive treatment choice on the prognosis of complete responders with p16+ and p16− oropharyngeal squamous cell carcinomas. (May 2022) - Muller, R. Grant; Hamill, Chelsea S.; Vu, Brandon; Thuener, Jason; Wasman, Jay; Li, Shawn; Fowler, Nicole; Rezaee, Rod; Lavertu, Pierre; Yao, Min; Burkitt, Kyunghee; Dorth, Jennifer; et al.
Highlights: p16+ status is a favorable biomarker in OPSCC following complete but not incomplete response. AJCC 8th edition staging has limited prognostic utility in OPSCC patients with complete response. Treatment choice and smoking history has an impact on the long-term outcomes of early-stage p16+ OPSCC patients with complete response. Abstract: Objectives: To identify predictors of overall survival (OS) in oropharyngeal squamous cell carcinoma (OPSCC) patients who achieved complete response (CR). Methods: We performed a retrospective study of OPSCC patients who achieved CR from a single academic medical center. Associations between OS, AJCC 8th edition staging system, definitive treatment choice, smoking history, and p16 status were assessed. Results: p16+ status was associated with favorable prognosis for CR (p < 0.001) but not non-CR (p = 0.67) patients. For early stage, p16+ OPSCC patients who achieved CR, surgery + adjuvant radiation (RT) treatment was more durable compared to concurrent chemoradiation (CRT), particularly in smokers. Conclusions: Curative intent treatment choice and smoking history has an impact on the long-term OS of the CR p16+ OPSCC cohort. Prospective studies to define the optimal multi-modality treatment option to manage p16+ OPSCC patients is needed.